Population structure and genetic variability within isolates of Grapevine fanleaf virus from a naturally infected vineyard in France: evidence for mixed infection and recombination - Vigne, Emmanuelle; Bergdoll, Marc; Guyader, Sébastien; Fuchs, Marc (Journal of General Virology, 2004)
The nematode-borne Grapevine fanleaf virus, from the genus Nepovirus in the family Comoviridae, causes severe degeneration of grapevines in most vineyards worldwide. We characterized 347 isolates from transgenic and conventional grapevines from two vineyard sites in the Champagne region of France for their molecular variant composition. The population structure and genetic diversity were examined in the coat protein gene by IC-RT-PCR-RFLP analysis with EcoRI and StyI, and nucleotide sequencing, respectively. RFLP data suggested that 55 % (191 of 347) of the isolates had a population structure consisting of one predominant variant. Sequencing data of 51 isolates representing the different restrictotypes confirmed the existence of mixed infection with a frequency of 33 % (17 of 51) and showed two major predominant haplotypes representing 71 % (60 of 85) of the sequence variants. Comparative nucleotide diversity among population subsets implied a lack of genetic differentiation according to host (transgenic vs conventional) or field site for most restrictotypes (17 of 18 and 13 of 18) and for haplotypes in most phylogenetic groups (seven of eight and six of eight), respectively. Interestingly, five of the 85 haplotypes sequenced had an intermediate divergence (0·036–0·066) between the lower (0·005–0·028) and upper range (0·083–0·138) of nucleotide variability, suggesting the occurrence of homologous RNA recombination. Sequence alignments clearly indicated a mosaic structure for four of these five variants, for which recombination sites were identified and parental lineages proposed. This is the first in-depth characterization of the population structure and genetic diversity in a nepovirus.